Cushing’s syndrome due to adrenocortical carcinoma: report of a case - Say, Burhan (The Turkish Journal of Pediatrics, 1958)
A case Cushing’s syndrome with adrenocortical carcinoma is presented and the diagnosis and treatment are discussed. The author wishes to acknowledge the kind assistance of Dr. Herbert Eckstein, F.R.C.S., in the preparation of this paper.